Water condensate morphologies on a cantilevered microfiber - Zhu, Fangqi (2020)
Water collection via fiber-based coalescers shows promise in mitigating increasing water scarcity, and most studies usually focus on the water collection by accumulating water through successive coalescences of fog in the absence of condensation. Here, we report on non-uniform condensate morphologies observed during air–vapor mixture condensation on a cantilevered microfiber. Due to the competition between thermal conduction resistance within the fiber and condensation heat transfer resistance on the fiber surface, the vapor diffusive flux along the fiber varies accordingly, engendering three representative condensate morphologies. We systematically examine the effects of fiber length, diameter, and material (constantan, 316L steel, and alumel) on these condensate morphologies. Scaling analyses are also provided to reveal the underlying physics. Our experimental investigations and theoretical analyses reported in this work shed more light on air–vapor mixture condensation mechanisms that could pave the way to future condensation-associated applications.